2019
DOI: 10.3389/fpls.2019.01345
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Plant Disease Resistance in Legumes

Abstract: The constant interactions between plants and pathogens in the environment and the resulting outcomes are of significant importance for agriculture and agricultural scientists. Disease resistance genes in plant cultivars can break down in the field due to the evolution of pathogens under high selection pressure. Thus, the protection of crop plants against pathogens is a continuous arms race. Like any other type of crop plant, legumes are susceptible to many pathogens. The dawn of the genomic era, in which high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 207 publications
(285 reference statements)
2
22
0
Order By: Relevance
“…Repeated experimental evidence supports the importance of pathogen complexes for the pea (Kerr, 1963;Shehata et al, 1983;Oyarzun and Van Loon, 1989;Xue, 2003;Wille et al, 2020) and other plant pathosystems (Lamichhane and Venturi, 2015;Abdullah et al, 2017). Notably, interactions of pathogens have significant implications for disease aetiology (Kerr, 1963;Willsey et al, 2018), plant resistance (Kankanala et al, 2019), and disease management (Gossen et al, 2016;You and Barbetti, 2019). Our results demonstrated that the composition of key microbial taxa of the PRRC in diseased pea roots was determined by conjoint effects of the soil and plant genotype.…”
Section: Discussionsupporting
confidence: 62%
“…Repeated experimental evidence supports the importance of pathogen complexes for the pea (Kerr, 1963;Shehata et al, 1983;Oyarzun and Van Loon, 1989;Xue, 2003;Wille et al, 2020) and other plant pathosystems (Lamichhane and Venturi, 2015;Abdullah et al, 2017). Notably, interactions of pathogens have significant implications for disease aetiology (Kerr, 1963;Willsey et al, 2018), plant resistance (Kankanala et al, 2019), and disease management (Gossen et al, 2016;You and Barbetti, 2019). Our results demonstrated that the composition of key microbial taxa of the PRRC in diseased pea roots was determined by conjoint effects of the soil and plant genotype.…”
Section: Discussionsupporting
confidence: 62%
“…ONT reveals an interesting tool for plants surveillance to detect plant virus routinely [47]. Finally, large-scale genomics studies of plant disease resistance were possible thanks to these high-throughput and cost-effective tools to clarify the interactions between legumes and pathogens [48]. At a gene scale, only few studies already reported successful cyt b sequencing by short-read NGS method for the purpose of pathogen resistance to fungicides studies.…”
Section: Resultsmentioning
confidence: 99%
“…The model legumes, soybean, and vetch (Aeschynomene evenia) are amongst plants that have been successfully transformed using this method [57]. Wang et al [57] and Kankanala et al [67] mention that the first application of the CRISPR/Cas9 technology was done using Agrobacterium rhizogenes, which resulted in the successful editing of both exogenous and endogenous DNA sequences. Explants that have been used for this purpose include callus tissue, leaf discs, flower tissue, and protoplasts, all of which are said to enable inheritance of the edited genome by the progeny, i.e., lead to stable transformation [66].…”
Section: Genome Editingmentioning
confidence: 99%